ANALISIS STRATEGI BERSAING PADA PABRIK GITAR CV DARIEOS KECAMATAN KEPANJEN, DI KOTA MALANG - Fatomy, Moch Dicky; djatno, Su (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2016)
This study discusses the analysis of competitive strategy on guitar factory CV. Darieos districts. Kepanjen, in the city of Malang in the face of its competitors in Malang. This study was preceded by analyzing the external environment and internal environment, strategy analysis was conducted through a strategic management approach by using tools, such as EFE matrix, IFE Matrix, Matrix CPM, SWOT Matrix, IE Matrix, and Grand Strategy. Then the results of the strategy formulation aids previously mentioned, compared and evaluated using the tools and Selection Phase Strategy Decision (Decision Stage) and QSPM (Quantitative Strategic Planning Matrix) to analyze the final result. From the analysis of the final results of this study suggest that CV. Darieos need to do a market development strategy to be able to compete with the other competitor. Â Keywords: Management strategy, competitive strategy